INVESTIGATING TEACHER’S PREFERENCES ON ONLINE TEACHING APPLICATIONS IN ESP SPEAKING CLASSES DURING COVID 19 PANDEMIC - Gunawan Tri Ramdani; Bambang Ruby Sugiarto (Journal of English Education Program (JEEP), 2022)
This research investigated teachers’ preferences on online teaching applications in ESP speaking classes during COVID-19 pandemic. A case study methodology was used in this research, and data were collected through transcribing and coding with observation and interviews with English teachers. It is analyzed by transcribing and coding with results from observations and interviews with English teachers in one of the Vocational High Schools in Pangandaran. The findings revealed that learning using ESP Speaking class is very important in student activity; so that English teachers must prepare and understand the teaching materials from English teachers that will be carried out. This did not made the students just silent and the gains achieved are stinging because of the lack of readiness of students in active learning in class. The application of ESP speaking classes should emphasize the teacher’s preferences on online teaching applications in ESP speaking classes during COVID-19 pandemic by motivating students.